Hope when life hurts most - Giglio, Louie; Redman, Matt.; Tomlin, Chris, 1972-; Hall, Charlie; David Crowder Band.; Passion Conferences; 268generation.; Sparrow Records (Roswell, Ga. : 268genration ; Brentwood, TN : Distributed by Sparrow Records, 2007)
"Life isn't easy. We experience problems and setbacks every day. But during the hardest parts of life ... the hope we find in [God] allows us to leverage our darkest moments for His fame."
CD: Blessed be your name (Matt Redman) -- Here is our king (David Crowder Band) -- You are God (Charlie Hall) -- Never let go (David Crowder Band) -- Amazing grace (My chains are gone) (Chris Tomlin).
DVD; Dolby digital.
Speaker, Louis Giglio.
Keywords: Hope -- Religious aspects -- Christianity -- Sermons; God -- Worship and love -- Sermons; Praise of God -- Sermons; God -- Attributes -- Sermons; Documentary videos; Speeches, addresses, etc; Sermons